Is Anyone Representing Non-resident Finnish Citizens in the Legislative Process of Finland? - Makkonen, Kimmo (Frontiers in Political Science, 2021)
This research paper examines the instances of representation of the expatriate Finnish citizen in the different stages of the legislative process in Finland: the preparation of law bills, the process in the Parliamentary committees and in the plenary sessions of the Finnish Parliament Eduskunta. The aim is to answer the questions how many and what kind of expatriate Finns issues there has been on the political agenda, when those issues were there, and who acted for the expatriates then. Here, the research approach is descriptive. Newly digitalized collections of legislative documents create novel opportunities to seek efficiently through a large number of records and find topics that have not gained much attention, in addition to the more obvious cases such as the dual citizenship or recently the postal voting. In Finland, the Finnish diaspora has not been a fervently debated issue and it is only rarely mentioned in the plenary debates of the Parliament. The data includes two kinds of sources, actions by the MPs and Government bills. In the Finnish case, the number of relevant documents is small. Therefore, including different types of text into a single study is necessary to find out the political forces that have influence on the issues concerning the Finnish citizen abroad.